Utility of telemedicine in COVID-19 pandemic: our experience at a tertiary cancer center in North East India - Das, Ashok Kumar; Boro, Sumanjit S.; Das, Anupam; Medhi, Partha Pratim; Kakati, Kaberi; Baishya, Nizara; Bhattacharyya, Mouchumee; Kataki, Amal Chandra (International Journal of Research in Medical Sciences, 2020)
Background: Telemedicine is a very useful tool of communication between the doctor and the patient. The aim of this study was to find out the utility of telemedicine during the lockdown period of COVID-19 pandemic in North East India. Methods: It is a cross sectional study among the cancer patients at our center on follow up or ongoing treatment and analysis of all the data acquired from telephonic conversation with our patients from 30th March, 2020 to 3rd May, 2020. Have contacted 4181 patients during this period over phone. All phone calls were done by respective department doctors. Results: From the demographic data, we get that 35.4% of patients were at good physical condition, 3.5% with poor general condition, 11.6% patients having ongoing treatment in our institute, 21.1% patients expired, 0.9% patients have nonmalignant diagnosis, 1.4% patients left the institute due to various reasons. Analyzed this data with brain storming sessions amongst the COVID-19 task force doctors and tried to find out solutions of each problem. Conclusions: Telemedicine cannot replace conventional method of in person treatment, but it proved to be a useful tool during the COVID-19 pandemic for patient follow up and treatment of cancer patients.